A visualização do invisível: beleza e mística em Santo Agostinho - Miguel, Roberto Pereira (2009)
In this dissertation we intend to analyse the way proposed, and developed, by Saint Augustine toward the visualization of the invisible God. That is Via Puchritudinis, the path of beauty, which is a mystic as much as an aesthetic way. The focus of this task is the aesthetic side of this journey, which becomes evident by the assertion made by Hans Urs von Balthasar on his aesthetic theology treatise called Glória. For him, Augustine s trajectory, especially his conversion, cannot be considered a walk from aesthetics to religious , but a conversion from a common aesthetic to another superior one (Balthasar, 1986, p. 97). Because, for Augustine, contemplating the beauty of the world and creation represents the first step of a trajectory toward an even more keenly discerning contemplation of God s beauty, from which creation s beauty is just a vestige. But when he identifies the absolute transcendent God with beauty, by the affirmation: Late have I loved You, Beauty so ancient and so new, late have I loved Thee! , Augustine makes this journey in a mystical way, in which history (God s action fulfilled by Jesus Christ) and prophecy (Scripture and His messengers) represents the two main pillars. Thus, we will also tackle Augustine s Via Pulchritudinis mystical side, in proportion to its relationship with the principal concept of this dissertation, which is, beauty. We understand that this concept of beauty, just as it was thought by Augustine, may be relevant to the present time, whereas the notion of beauty, nowadays, seems to have left behind all its transcendent aspects to shut itself up just in what is imanent, that is, body and matter